THE EFFECTIVENESS OF THE STAD METHOD IN THE TEXT OF WRITING LESSONS ENGLISH PROCEDURE IN CLASS IX STUDENTS OF JUNIOR HIGH SCHOOL PLUS AL-KAUTSAR MALANG - Sholikha, Aprilla Iswatul; Pujiyanti, Pujiyati (English Edu: Journal of English Teaching and Learning, 2023)
This study aims to improve the ability to compose procedural texts for students of class IX SMP Plus Al-Kautsar Malang by applying the learning method using the Student Team-Achievement Division (STAD) method. This research uses Classroom Action Research which is conducted in two cycles, with each cycle consisting of planning, implementation, observation and reflection. The subjects of this study were students of class IX SMP Plus Al-Kautsar Malang in the odd semester of the 2022/2023 academic year, totaling 17 students. Data collection in this study was carried out in two cycles. Cycle 1 shows the percentage of learning outcomes of 52.9%, from the data it is known that 8 students are still below the minimum completeness criteria. Then in cycle 2 the percentage of learning completeness reached 100%. So it can be concluded that there is a very significant increase in learning outcomes from the use of the STAD learning method.